2015
DOI: 10.1128/jvi.00129-15
|View full text |Cite
|
Sign up to set email alerts
|

Anti-V3/Glycan and Anti-MPER Neutralizing Antibodies, but Not Anti-V2/Glycan Site Antibodies, Are Strongly Associated with Greater Anti-HIV-1 Neutralization Breadth and Potency

Abstract: The membrane-proximal external region (MPER), the V2/glycan site (initially defined by PG9 and PG16 antibodies), and the V3/glycans (initially defined by PGT121-128 antibodies) are targets of broadly neutralizing antibodies and potential targets for anti-HIV-1 antibody-based vaccines. Recent evidence shows that antibodies with moderate neutralization breadth are frequently attainable, with 50% of sera from chronically infected individuals neutralizing >50% of a large, diverse set of viruses. Nonetheless, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…Consistently, a recent study demonstrated that neutralizing antibodies to these two epitopes were associated with greater serum neutralization breadth and potency in a large patient cohort (88). However, a meaningful comparison of vaccine design strategies and epitope-specific antibody responses would require immunogens that have been optimized both structurally and antigenically.…”
Section: Discussionsupporting
confidence: 63%
“…Consistently, a recent study demonstrated that neutralizing antibodies to these two epitopes were associated with greater serum neutralization breadth and potency in a large patient cohort (88). However, a meaningful comparison of vaccine design strategies and epitope-specific antibody responses would require immunogens that have been optimized both structurally and antigenically.…”
Section: Discussionsupporting
confidence: 63%
“…Given that antibodies to the oligomannose patch on HIV-1 are major contributors to neutralization breadth and potency in many HIV-infected individuals [59][60][61] , we feel that these efforts are worthwhile as part of the broader endeavor of developing an effective HIV vaccine component to elicit bnAbs.…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation bnAb 10E8 recognizes the conserved membrane-proximal external region (MPER) of the gp41 subunit of the envelope glycoprotein (Env) (2-5), resulting in one of the highest levels of HIV-1 neutralization reported to date (1,(6)(7)(8). Antibodies against this vulnerable site also mediate the neutralization breadth and potency of sera from a subset of HIV-1-infected individuals (8,9). Despite reported similarities in the epitope binding profile with the first-generation anti-MPER bnAb 4E10, 10E8 displays high neutralization potency and very limited, if any, polyreactivity in comparison (8, 10).…”
mentioning
confidence: 99%